PENGARUH STRUCTURAL SOCIAL CAPITAL, COGNITIVE SOCIAL CAPITAL DAN RELATIONAL SOCIAL CAPITAL TERHADAP KINERJA KARYAWAN PT. BOMA BISMA INDRA KOTA PASURUAN - Achmad Agung; Vita Fibriyani; Tahajjudi Ghifary (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2023)
Human resources are in important element to the company, failure to manage human resources can hamper company goals. To get good employee performance, PT. Boma Bisma Indra at Pasuruan district would have to make a lot of effort to improve employee performance. Among other things, improving the relationships between employees is the social capital relationship. This study aimed to find out the effect of the structural social capital, cognitive social capital and relational social capital on employee performance in PT. Boma Bisma Indra at Pasuruan district. This study, using quantitative research methods and 78 respondents take samples. Data collection techniques carried out through library research, observation, interviews and questionnaires. The results showed that there was a contribution of the independent variable to the dependent variable of 75% with the results of the calculated f test suggests that the structural social capital, cognitive social capital and relational social capital have significant on employee performance with significant 0,000. The test t showed that structural social capital have significant on employee performance with significant 0,001. Cognitive social capital have significant on employee performance with significant 0,013. Relational social capital significant on employee performance with significant 0,001.